Academic Collaboration with African Universities - Boeren, Ad (International Higher Education, 2014)
Over the years, collaboration between academic institutions in the global North and institutions in Africa has been characterized by an evolutionary process from pure capacity building to equal partnerships, from social commitment to matching interests, and from specific needs to global strategies. A brief review of this process against the backdrop of global changes and higher education challenges provides a better understanding of the present opportunities and constraints.